2022
DOI: 10.3390/ijerph19021001
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Skeletal Muscle Mass and Intracellular Water as Undesired Outcomes of Weight Reduction in Obese Hyperglycemic Women: A Short-Term Longitudinal Study

Abstract: The current study is focused on the influence of hyperglycemia on weight loss in obese premenopausal women. Specifically, the study evaluated the impact of a six-month individualized low-calorie diet combined with moderate exercise on weight reduction and glucose metabolism in obese women with normoglycemia compared to obese women with moderate hyperglycemia. The results indicated that patients with normoglycemia achieved a successful weight loss, which was connected to a decrease in adipose tissue and reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…However, those patients who lost more than 5% of SMM had the highest glucose and fructosamine levels and HOMA-IR before the program. This indicates the influence of glycemic status on tissue loss and supports our previous results [27].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, those patients who lost more than 5% of SMM had the highest glucose and fructosamine levels and HOMA-IR before the program. This indicates the influence of glycemic status on tissue loss and supports our previous results [27].…”
Section: Discussionsupporting
confidence: 93%
“…Previous findings indicate that reducing visceral fat is the most favorable metabolically, whereas reducing skeletal muscle or water is less favorable [26][27][28]. Our previous research also revealed that weight reduction through a balanced diet and exercise is more effective in normoglycemic compared to hyperglycemic women with obesity.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation